Intraoperative photodynamic control of radical prostatectomy - I. V. Chernyshev; Y. V. Samsonov; I. I. Abdullin; D. V. Altunin; K. K. Kallaev (Бюллетень сибирской медицины, 2012)
Based on the experience of photodynamic diagnosis with a photosensitizer «Alasens» during the execution of open and laparoscopic radical prostatectomy were obtained and analyzed the clinical results of the study. The method of photodynamic diagnostics enables intraoperative detection of tumor-affected areas of the bed of the prostate with subsequent resection. The method is promising for reducing the incidence of positive surgical margins.